The Baltic States and their region : new Europe or old? - Smith, David J. (David James), 1968- (On the boundary of two worlds, 2005)
With EU and NATO membership for the Baltic States now a reality, this volume examines the relationship of the three countries, their constituent peoples and their surrounding region to the wider Europe, both historically and in the period since 1991. In particular, the contributors seek to locate the Baltic area within the manifold debates surrounding the concepts of "new" and "old" Europe, including those occasioned by the current conflict in Iraq. Covering issues of identity, sovereignty, minority rights, security and relations with Russia the work assesses the likely contribution of this re.